Mnemonic techniques and lie detection: Accuracy of truth and deception judgments in repeated accounts - Izotovas, Aleksandras; Vrij, Aldert; Strömwall, Leif A. (Psichologija, 2021)
This study was an examination into whether the use of memory-enhancing techniques (mnemonics) in interviews can be helpful to distinguish truth tellers from liars. In the previous study (Izotovas et al., 2018), it was found that when mnemonic techniques were used in the interview immediately after the event, truth-tellers reported more details than liars in those immediate interviews and again after a delay. Moreover, truth-tellers, but not liars, showed patterns of reporting indicative of genuine memory decay.In the current experiment, participants (n = 92) were asked to read the repeated statements reported by participants in the Izotovas et al.’s (2018) study and decide whether the statements they read were truthful or deceptive. One group of participants (informed condition) received information about the findings of the previous study before reading the statement. The other group received no information before reading the statement (uninformed condition). After participants made veracity judgements, they were asked an open-ended question asking what factors influenced their credibility decision. Although truthful statements were judged more accurately in the informed condition (65.2%) than in the uninformed condition (47.8%), this difference was not significant. In both conditions deceptive statements were detected at chance level (52.2%). Participants who relied on the self-reported diagnostic verbal cues to deceit were not more accurate than participants who self-reported unreliable cues. This could happen because only the minority of participants (27.4%) in both conditions based their decisions on diagnostic cues to truth/deceit.
Keywords: Lie detection accuracy; Deception cues; Verbal lie detection; Mnemonic techniques; Repeated interviewing